Teach Us, Amelia Bedelia - Parish, Peggy; Sweat, Lynn. (New York : Scholastic, 1995)
The very literal minded Amelia Bedelia becomes a substitute teacher for a day.
aReprint. Originally published: New York : Greenwillow Books, c1977.
a"Grades 2 & 3"--Cover.
Keywords: Schools -- Fiction; Teachers -- Fiction; Humorous Stories